The Irwin handbook of telecommunications - Green, James H. (James Harry) (Irwin Professional Publisher, 1997)
"The Irwin Handbook of Telecommunications, 3rd Edition provides the foundation you'll need to understand the North American telecommunications network. It illustrates how the telecom puzzle pieces function as a whole and the role of each individual piece. While providing comprehensive coverage, James Harry Green focuses on a wide scope of the major elements of telecommunications that can help you establish a base of information." "Revised and thoroughly updated, this edition puts the telecommunications professional "in the know" about the latest industry technologies and their function in the grand scheme." "With a complete list of North American area codes, country codes, telecommunications standards, and suppliers and their products, The Irwin Handbook of Telecommunications serves as an easy-to-reference guide for frequently used information."--BOOK JACKET